The Current Position of Neuromarketing as a Tool of Marketing and Communication Strategy - Ladislav Pátík (Communication Today, 2025)
Neuromarketing is a tool used to investigate real consumer preferences that are not subjectively influenced, e.g. bias towards a certain brand, marketing communication tools, etc. It studies brain functions when deciding to buy a product. The goal is to find and identify the differences between the customer’s conscious assertion and subconscious behaviour. It monitors how the brain reacts to certain stimuli contained in an advertisement, brand, etc. For this, it uses studies that examine the influence of marketing stimuli on consumer reactions. The goal of our study is to provide an objective and comprehensive overview of new scientific findings that point to certain gaps in research methods and thinking about consumer behaviour and decision-making. We focus on the field of neuromarketing in general, on its methods, the concept of intuitive consumer behaviour. The core parts are practical applications of neuromarketing in the field of marketing and marketing communication. The research part describes the course and results of the applied experiment, using two methods of neuromarketing research to influence the senses of the consumer and to find the differences between conscious and unconscious decision-making, and at the same time, how these findings can manifest themselves in the area of ​​marketing and communication strategy. Key findings are clearly summarised in the summary and conclusion.